A Neglected Dimension of Medical Tourism Destination Impacts: A Synthesis of Observations and Convictions - Joseph, Sindhu (Atna Journal of Tourism Studies, 2018)
Medical tourism based on transnational journeys for health care, cure, and well-being is being widely discussed in the literature. As a fast-developing phenomenon, there are different views and perspectives on the concerns of medical tourists and various impacts created in destination areas. This paper critically observes the exertions of medical tourism on destination areas in the light of economic and socio-cultural influences. This paper tries to bring out the muddles of the phenomenon based on empirical research. The paper suggests that the socio-cultural impact of medical tourism on the health care of the poor local people must be viewed seriously and calls for rigid and efficient legislation from the authorities to enable and strengthen the public healthcare system.